OUTPATIENT REGISTRY OF PATIENTS WITH ACUTE MYOCARDIAL INFARCTION (PROFILE-IM): DATA ON PREHOSPITAL THERAPY IN COMPARISON WITH THE LIS-3 REGISTRY - N. P. Kutishenko; E. P. Kalaydzhyan; D. P. Sichinava; V. A. Evdakov; S. Yu. Martsevich (Столичная издательская компания, 2018)
Aim. To study the quality of prehospital therapy in patients with a history of acute coronary syndrome/acute myocardial infarction (ACS/AMI), and included in 2 registers: LIS-3 and PROFILE-IM.Material and methods. Data on therapy before the reference ACS in the hospital register LIS-3 (Lyubertsy town, 01.11.2013-31.07.2015) and in the AMI outpatient registry PROFILE-IM (Moscow city polyclinic N9) were compared. Anonymized data from the case histories (320 patients from the LIS-3 registry) and outpatient charts (160 patients from the PROFILE-IM register) were analyzed.Results. Angiotensin-converting enzyme inhibitors/angiotensin receptor blockers before AMI in patients from PROFILE-MI were prescribed significantly more often than in the LIS-3 registry (49.4% vs 39.4%, respectively, p<0.05), as well as calcium channel blockers - 6.7% vs 5.3%, respectively (p<0.05). The frequency of prescription of statins, antiplatelet agents and anticoagulants before reference AMI in patients of both registers did not differ significantly. Assessment of adherence to treatment was performed in the PROFILE-IM registry. 56 (35.0%) patients did not take medication. Among cases with pharmacotherapy only 41 (39.4%) patients had regular taking, and 24 (23.1%) took medication in worsening health, 39 (37.5%) had only short medication courses. Similar data were revealed in patients already having ischemic heart disease.Conclusion. Primary and secondary drug prevention of AMI in both registries did not meet modern clinical guidelines. This was especially true for patients with already established ischemic heart disease and to the greatest extent, according to both registries, refers to drugs from the statin group.